Design and Optimization of Nanostructured Lipid Carriers for Quercetin in Skin Lightening Applications - Ressa Marisa; Widji Soeratri; Tristiana Erawati Munandar (Universitas Airlangga, 2025)
Background: Quercetin, a potential skin-lightening agent, reduces intracellular and fungal tyrosinase activities. However, its poor water solubility and limited skin permeability hinder its applications. Nanostructured lipid carriers (NLCs), which are composed of biocompatible and biodegradable lipids, enhance drug stability and skin penetration. The lipid type, surfactant concentration, and formulation parameters influence NLC stability. Objective: This study aimed to optimize NLC formulations for quercetin delivery by evaluating their organoleptic properties, particle size, polydispersity index (PDI), and pH. Methods: NLCs were prepared using 10% total lipids (4% solid and 6% liquid lipids) and surfactant mixtures at varying concentrations via High Shear Homogenization. Initial formulations using myristic acid and castor oil were unstable and underwent phase separation within five days. Results: Substituting the solid lipid with a 1:3 combination of beeswax and cocoa butter produced a stable formulation during storage at room temperature. The lipid and surfactant compositions significantly influenced the particle size and PDI. While the pH remained stable, statistical analysis revealed significant changes in particle size and PDI across the formulations. Conclusion: Optimized NLC formulations for quercetin delivery demonstrated improved stability and potential for effective skin lightening. Further research is warranted to evaluate the in vivo efficacy and scalability of this approach.